Policies for international transmission investment: Unlocking North Africa's renewable energy portfolio - for local use and international exchange. Final report - Karsten Neuhoff; Christian Winzer; Loredana Sasso (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
The study aims to identify suitable regulatory frameworks and business models for transmission investment to enable international exchange and local use of renewable energy across the EU and MENA regions. The analysis explores how policy frameworks can support the realization of individual transmission lines and their use to support renewable project investment and energy transport in the short-term, e.g. next ten years. The current ten year network development plan of ENTSO-e envisages such lines between Italy and Tunisia and between Italy and Algeria with a total capacity of 1.5 GW. An interconnection of similar scale already exists between Spain and Morocco. Grid and renewable projects could facilitate closer cooperation between the EU and MENA regions to support their economic development, job prospects and reducing reliance on domestic subsidized gas purchases. For the longer-term, large scale transmission between EU and MENA can lead to large cost savings, as it can enable an arbitrage in the daily and seasonal profiles of wind and solar plants and demand in the EU and MENA countries, and can allow to access some of the better resource potentials (DII, 2012). Such large scale energy cooperation requires early projects to develop trust, experience on institutional and technology sides and continuous dialog among all stakeholders involved. Therefore policy frameworks to support individual projects also need to be assessed with regard to their ability to contribute towards such a longer-term perspective.
urn:nbn:de:0084-diwkompakt_2013-0748
Keywords: 330